IDIOPATHIC INFANTILE HYPERCALCEMIA – CASE REPORT - Palchevska, Snezana; Spasevska, Simonida; Jovanovska, Jana; Tasic, Velibor; Aluloska, Natasha (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Idiopathic Infantile Hypercalcemia (IIH) is a rare genetic disease which cardinal features is failure to thrive, polyuria, dehydration, vomiting, seizures, lethargy, comma and if unrecognized and untreated may result in death. Laboratory investigations show hypercalcemia, hypercalciuria, elevated values of 1, 25 (OH) D3 and suppressed levels of parathormon.  Ultrasound study usually reveals bilateral medullary echogenicity typical for nephrocalcinosis. Emergency treatment consists from large hydration, prednisolone, calcitonin and biphosphonates, which were used with success. In this report we present a 6 month old female infant who came to our attention due to growth delay as a consequence of  polyuria, vomiting and poor apetite.Dietary management with withdrawal of vitamin D and reduction of calcium intake significantly improved  the general health status and normalized the serum biochemistry. The diagnosis was established with mutational analysis of the CYP24A1 gene.   Key words : idiopathic infantile hypercalcemia, CYP24A1 , vitamin D, nephrocalcinosis. https://doi.org/10.55302/JMS2141029p